Особенности экономической эффективности инноваций - Мелень, Елена Валентиновна; Мелень, Б. С.; Юрченко, Л. А. (НТУ "ХПИ", 2008)
The method of calculation of effect innovations, based on comparison of results of their development to expenses, allows to make a decision on expediency of use of new development.
Keywords: освоение инноваций; затраты; маркетинг; продукция конкурентоспособная